Political Economy of Indonesia: Analyzing the Role of Economic Elites in Shaping Public Policy - Pim Vermeulen; Putri Kusuma Dewi (Artes Libres Institutum, 2025)
Indonesia's political economy has been deeply influenced by the concentration of economic power in the hands of a few elites, both during the New Order regime and in the post-Reformasi era. This paper explores the ongoing role of economic elites in shaping public policy and political outcomes in Indonesia. By examining the interplay between business interests, political parties, and state institutions, the study highlights how economic elites influence decision-making processes, public policy, and national development. The paper critically assesses the impact of oligarchy on Indonesia’s economic growth, poverty reduction, and governance, exploring the ways in which elite capture affects democratic functioning. The research contributes to the broader field of political economy by offering insights into the challenges of addressing wealth inequality and promoting inclusive development in Indonesia. It also discusses potential policy reforms to mitigate the undue influence of economic elites on public policy.